Aprendizaje significativo y su incidencia en el rendimiento académico en los estudiantes de 4to año de EGB de la UE Emigdio Esparza Moreno, Babahoyo. 2022 - Suarez Pisacome, Carolyn Yanina (2022)
The learning process has an important role in the formation of the student, because if it is not adequate, the student will not obtain optimal academic performance; that is, they will lack important abilities and skills that help the individual function adequately, both in the educational and social context. The objective of this case study is based on determining how significant learning affects the academic performance of 4th year EGB students from the EU Emigdio Esparza Moreno, Babahoyo 2022, due to the fact that the absence of Innovative pedagogical strategies that allow the development of meaningful learning. The methodology used is made up of the types of descriptive, field and documentary research, while the techniques were direct observation and interview, which were directed to 57 students and two teachers in charge of the academic level analyzed, where the main results were the absence of inappropriate climate within the classroom process, which limits the development of learning; In addition, it was established that the students do not have an appropriate academic achievement, for which it is necessary to establish better educational actions by the teachers and greater accompaniment by the parents.